Burundi Poverty Assessment - World Bank (World Bank, Washington, DC, 2021)
Since early 1990’s, Burundi underwent periods of repetitive socio-political tensions, characterized by violent conflicts within the population, positioning the country as a fragile State and one of poorest in the World. While there have been progress toward economic recovery and some improvements in households living conditions since the restoration of peace in 2006, the country continues to bear out the consequences of fragility. A large proportion of the population continues to suffer from severe deprivations in basic consumption needs. National development policies, including the second Poverty Reduction Strategy (PRSP-II), put an important emphasis on reducing poverty and vulnerability, enhancing equity in education and health access, and promoting more inclusive growth. This report uses the availability of the ECVMB 2013-2014 to provide a robust diagnostic of poverty and inequality in Burundi and bring new evidence to better inform policies aimed at poverty alleviation and equity. This is complemented by data from various sources, including previous household surveys and the National Agricultural Surveys (ENAB) for 2011-2012 and 2012-2013. The first chapter of the report will provide an overview on the country’s context and the remaining chapters are as follows. Chapter two assesses the incidence and structure of consumption poverty and inequality using the most recent survey, ECVMB 2013-2014. The third chapter examines the evolution of living conditions since 2006. Chapter four examines the linkage between governance and fragility and their impact on persisting poverty. Chapter five analyzes the labor market situation and investigates the informal employment. The last two chapters focus on agriculture, environmental sustainability, and climate change and their impact on poverty.